2010
DOI: 10.1111/j.1365-2362.2010.02358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetyl‐L‐carnitine and oxfenicine on aorta stiffness in diabetic rats

Abstract: Acetyl-L-carnitine, but not oxfenicine, attenuates aortic stiffening and cardiac hypertrophy, possibly through its decrease of lipid oxidation-derived MDA/TBARS in the rats with insulin deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 47 publications
0
18
1
Order By: Relevance
“…Oxfenicine (4-Hydroxy-L-phenylglycine) has been successfully used as an inhibitor of fatty acid oxidation, but with contradictory outcomes [22,23]. A few studies have reported negative outcomes associated with the experimental use of oxfenicine in healthy lean animals [23][24][25][26]. The underlying mechanism(s) for these effects remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Oxfenicine (4-Hydroxy-L-phenylglycine) has been successfully used as an inhibitor of fatty acid oxidation, but with contradictory outcomes [22,23]. A few studies have reported negative outcomes associated with the experimental use of oxfenicine in healthy lean animals [23][24][25][26]. The underlying mechanism(s) for these effects remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Previous work from our laboratory demonstrated that OXF, but not ALC, elevates R p in the diabetic peripheral arteries, which parallels its increase in plasma levels of FFA [17]. By contrast, ALC attenuates the diabetes-related arterial stiffening and cardiac hypertrophy through its ability to reduce aorta levels of MDA/TABRS in the DM.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, the reduced plasma FFA and cardiac MDA levels from ALC may be responsible for the prevention of diabetes-related damage in the myocardial contractility. By contrast, in the absence of any significant changes in cardiac MDA content, the already high plasma levels of FFA augmented when the DM was treated with OXF [17]. OXF might accordingly be expected to exert no benefit to the diabetic heart and even worsen the contractile status of the LV.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Considering the role of oxidative stress in this process, antioxidant treatment can be expected to reduce/ prevent organ damages in DM. It has been shown in recent studies that antioxidant agents such as apocynin, lipoic acid, simvastatin,coenzyme Q10 and acetyl L-carnitine have positive effects in DM (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%